Trends in the scientific publication on retirement: A brief report - Barbosa, Leonardo Martins; Sampaio, Ricardo Barros; Murta, Sheila Giardini (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2020)
This study aimed to synthesize the scientific publication on retirement between 1991 and 2015. Analysis were done using the software Iramuteq to systematize papers extracted from Scopus database that included the word retirement (N = 18,362). Results have shown that North American and European countries are among the most productive. Health and economics are the most researched fields and are interconnected by a common interest in public policy. Relevant topics, such as retirement education, were absent from the main results. It is discussed that the number of publications is associated with national investment in research and development and has little relationship with the proportion of elderly individuals. A broader and interdisciplinary research agenda is recommended.